EgMLP1 Gene Expression in Oil Palm Ramet Infected with Ganoderma boninense - Yasinta Ratna Esti Wulandari; Felicia Felicia; Arild Ranlym Arifin; Antonius Suwanto (Indonesian Oil Palm Society /IOPS (Masyarakat Perkelapa-sawitan Indonesia /MAKSI), 2018)
Oil palm (Elaeis guineensis) is an important crop commodity in Indonesia. However, the effort to increase its production is hindered by basal stem rot (BSR), a devastating disease caused by Ganoderma boninense. The early symptoms of G. boninense infection cannot be observed with naked eyes. It can only be observed at the later stage of the infection. By the time the symptoms appear, the palm is beyond recovery. Hence an early detection technique is essential for effective management of BSR in oil palm. The aim of this research is to analyze and compare the gene expression profile of a defense-related gene encoding early methionine-labeled polypeptide (EgEMLP1) by using quantitative reverse-transcription PCR between the leaves of untreated and treated oil palm cultures with G. boninense. First, G. boninense was isolated and inoculation on oil palm cultures, then RNA isolation was conducted on both oil palm cultures from 3 to 7 weeks post infection (wpi) and purified RNA was used for cDNA synthesis. Finally, EgEMLP1 gene expression was measured using qRT-PCR. The result showed that the expression of EgEMLP1 gene had increased 5.65, 15.66 and 17.96 fold at 3, 5 and 7 wpi compared to those of controls. Furthermore, the result also showed that direct infection method on in vitro oil palm cultures shorten the time needed to infect G. boninense to oil palm compared to rubber wood block method. With less process, direct inoculation method can be an alternative in gene expression in oil palm ramets infected with G. boninense research and up-regulated EgEMLP1 gene expressed has the potential to be developed as a biomarker for early detection of G. boninense infection.